Time-Varying Return and Risk in the Corporate Bond Market - Chang, Eric C.; Huang, Roger D. (Journal of Financial and Quantitative Analysis, 1990)
This paper examines the pricing of exchange-traded long-term corporate bond portfolios. Observable instruments measuring the term structure of interest rates, levels of bond and stock prices, and a January dummy are found to predict excess returns on corporate bonds. An intertemporal asset pricing model with changing expectations and unobservable factors is then estimated for the predictable excess returns using Hansen's Generalized Method of Moments. The results show that a multibeta linear time-varying model of con? ditional expected returns with constant betas can successfully value corporate bonds. Spe? cifically, the tests indicate the presence of two time-varying hedge portfolios. The data, however, support a single latent variable specification when all January observations are excluded. This result suggests the existence of a strong January seasonal in one of the latent variables.